The illusion of the Holy Grail of decoupling: Are there countries with relatively high SDGI and moderately low ecological footprint? - László Radácsi; Cecília Szigeti (Environmental and Sustainability Indicators, 2024)
The development of sustainability indicators at the national level emerged due to the limitations of using GDP as a measure of well-being, sustainability, and resilience. Over time, various indicators and rankings have been formulated, with a shift in focus from solely economic growth to a more encompassing perspective. The objective of this study was to create a new ranking, based on the integration of two methodologies, namely UN Sustainable Development Goals Index (SDGI), and the Global Footprint Network's Ecological Footprint (EF), in order to identify meaningful clusters of countries based on both measures. Hierarchical clustering was utilized to group countries, while the Nearest Neighbour method was employed to filter out outliers, and the Ward method determined the final clusters. Additionally, the Pearson's correlation coefficient was calculated to assess the relationship between the 17 SDGIs and the EF. The clustering outcomes revealed that a three-cluster solution can be considered satisfactory. The results obtained with the new method demonstrate that the environmental dimension of SDGI is a sufficient metric for environmental sustainability in terms of ranking countries.